An Enhancing Students Reading Comprehension by Using Cooperative Integrated Reading and Composition (CIRC) - Abdul Rahman R.; Enni Enni; Syahban Mada Ali; Badriah Badriah (Edumaspul: Jurnal Pendidikan, 2023)
Reading comprehension simply understanding what has been read. There are many strategies that can be applied by the teacher to maximize their role in the classroom, but most of them did not try to find a variety of methods. One of the methods that can be used is Cooperative Integrated Reading and Composition (CIRC). Cooperative Integrated Reading and Composition (CIRC) is a method that students work together to accomplish shared goals. They work together to maximize their own and each other’s learning. In cooperative groups, students work together on specific tasks or projects in such a way that all students in the group benefit from the interactive experience. Since learners are different in their intellectual capacity, their attitude, and their linguistic methods. Furthermore, cooperative learning is a great way to engage English language learners in learning both language and content. This research will be quasi-experiment research. In this research, pre-test and post-test will be administered. To obtain the data, the researcher will use a reading comprehension test and questionnaire. This research will focus on how Cooperative Integrated Reading and Composition (CIRC) enhance reading comprehension. Therefore, the researcher decides to give the title of this research namely “Enhancing Students’ Reading Comprehension by Using CIRC”. The Output target of this research is “published in the national scientific non-accredited journal, 1st-yearsst year target: Accepted/Published”. Level of Technology Readiness (TKT), 1st-yearsst year Target: Scale 2.